Providing trusted COVID-19 sources in social media: Establishing Indonesian Pediatric Society's social media ecosystem - Hikari Ambara Sjakti; Catharine Mayung Sambo; Tiara Annisa P. Mardhani; Saskia Octariza Ruslim; Clara Petrisiela I. Atmaja; Piprim Basarah Yanuarso; Aman Bhakti Pulungan (Wolters Kluwer Medknow Publications, 2023)
Introduction: During the COVID-19 pandemic, social media has become the main platform to find information in every aspect. It is important for professional organizations to develop social media in their field. The Indonesian Pediatric Society (IPS) has distributed information through various social media channels, like Professional Official Website. It is formed to reach various target users, hoping that information will be spread evenly among all Indonesian parents. This study aims to describe how the IPS media ecosystem provides trusted health information, which can help disseminate health information among parents and health practitioners during the pandemic. Methods: The study used a descriptive design using IPS social media platforms such as Professional Official Website (idai.or.id), Instagram, Facebook, Twitter, YouTube, Public Official Website (anakindonesiasehat.com), and Telemedicine Mobile Application (PrimaKu). Results: The IPS's social media accounts have shown significant growth during the pandemic showing that people are more aggressively seeking information from trusted sources. A public education-related Instagram live footage titled "Drugs and Vitamins for children with COVID-19 during quarantine at home" has become the most demanded material for social media users. This shows that social media is an excellent platform for health promotion. Conclusion: IPS, as a professional organization, needs to provide accurate, reliable, and up-to-date information on its social media and should take advantage of this opportunity to disseminate the latest guidelines and educate the public more thoroughly, especially parents, to help them obtain information on children's health.